Development of Communicative Abilities of Secondary School Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The development of communicative abilities in secondary school students is crucial for their academic success and social integration. Didactic games, as a pedagogical tool, offer an engaging and effective method for fostering communication skills in students. This article reviews the theoretical foundations of using didactic games in education and examines empirical evidence supporting their efficacy in enhancing communication skills among secondary school students. Additionally, it discusses practical implications and recommendations for educators to incorporate didactic games into their teaching practices to promote the holistic development of students.